2012
DOI: 10.1002/cbf.2856
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine prevents necrotic and apoptotic death of rat thymocytes via ouabain‐sensitive Na/K‐ATPase

Abstract: It is known that ouabain, a selective inhibitor of Na/K-ATPase, can cause not only activation of signal cascades, which regulate the cell viability, but also can cause free radical accumulation, which can evoke the oxidative stress. We have shown that nanomolar concentrations of ouabain result in the temporary increase in the level of intracellular free radicals but the millimolar concentration of ouabain induces a stable intracellular accumulation of free radicals in rat thymocytes. The increasing level of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was also observed that this effect is related to CD69 increased expression, a molecule associated with cell activation, induced by ouabain (Rodrigues-Mascarenhas et al, 2003 ). Additionally, ouabain induces in vitro intracellular free radicals accumulation and thymocytes death (Smolyaninova et al, 2013 ). In vivo , ouabain synergizes with hydrocortisone increasing T lymphocyte precursors death by apoptosis (Rodrigues-Mascarenhas et al, 2006 ), which reinforces its role as a stress-related hormone.…”
Section: Ouabain and Immune Systemmentioning
confidence: 99%
“…It was also observed that this effect is related to CD69 increased expression, a molecule associated with cell activation, induced by ouabain (Rodrigues-Mascarenhas et al, 2003 ). Additionally, ouabain induces in vitro intracellular free radicals accumulation and thymocytes death (Smolyaninova et al, 2013 ). In vivo , ouabain synergizes with hydrocortisone increasing T lymphocyte precursors death by apoptosis (Rodrigues-Mascarenhas et al, 2006 ), which reinforces its role as a stress-related hormone.…”
Section: Ouabain and Immune Systemmentioning
confidence: 99%